2008
DOI: 10.1038/bmt.2008.221
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis for the treatment of steroid refractory acute GVHD

Abstract: Extracorporeal photopheresis (ECP) was given to 23 patients with steroid-refractory acute GVHD (aGVHD, grade II (n ¼ 10), III (n ¼ 7) or IV (n ¼ 6)). The median duration of ECP was 7 months (1-33) and the median number of ECP cycles in each patient was 10. Twelve patients (52%) had complete responses. Eleven patients (48%) survived and 12 died, 10 of GVHD with or without infections and two of leukaemia relapse. The average grade of GVHD was reduced from 2.8 (on the first day of ECP) to 1.4 (on day þ 90 from EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 36 publications
(37 reference statements)
8
106
1
1
Order By: Relevance
“…28 Extracorporal photochemotherapy has been reported to induce CRs in up to 61 and 40% of patients with GI aGVHD, respectively, depending on GVHD grade. 29,30 The use of MSCs has been of emerging interest in the treatment of aGVHD because of their immunoregulatory potential. Le Blanc et al 31 achieved CR rates of 55% (30/55) in a phase II study.…”
Section: Discussionmentioning
confidence: 99%
“…28 Extracorporal photochemotherapy has been reported to induce CRs in up to 61 and 40% of patients with GI aGVHD, respectively, depending on GVHD grade. 29,30 The use of MSCs has been of emerging interest in the treatment of aGVHD because of their immunoregulatory potential. Le Blanc et al 31 achieved CR rates of 55% (30/55) in a phase II study.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant-related mortality was only 14 % in patients treated with ECP while 73 % in patients who were not [104]. Other retrospective studies have also shown benefit of ECP in treatment of aGVHD [105]. ECP is safe, without any increase in rate of infections, secondary malignancies or mortality [106].…”
Section: Extracorporeal Photopheresis (Ecp)mentioning
confidence: 99%
“…A clinical benefit has first been suggested in patients with chronic GVHD, and several prospective or retrospective studies reported promising results in patients with steroid refractory acute GVHD (aGVHD). 1,2 The theoretical advantages of ECP are no increased risk of infection, no adverse events such as metabolic or organic impairment and potential preservation of the GVL effect. 2 Moreover, as its immunomodulatory effects do not rely on the destruction or inactivation of cells but rather on the generation of active immune cells, these effects can be sustained and no severe flare-up of GVHD has been reported.…”
mentioning
confidence: 99%
“…1,2 The theoretical advantages of ECP are no increased risk of infection, no adverse events such as metabolic or organic impairment and potential preservation of the GVL effect. 2 Moreover, as its immunomodulatory effects do not rely on the destruction or inactivation of cells but rather on the generation of active immune cells, these effects can be sustained and no severe flare-up of GVHD has been reported. 1 In a recent retrospective study, Calore et al 3 have compared the outcome of children with aGVHD depending on whether they had been treated with ECP or not.…”
mentioning
confidence: 99%
See 1 more Smart Citation